2022
DOI: 10.23950/jcmk/12260
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus-19 phobia and health literacy in adults: A descriptive-correlational study

Abstract: The aim of this study was to determine the levels of health literacy (HL) and COVID-19 Phobia (C19P-S) in adult individuals and was to evaluate the relationship between health literacy and coronavirus-19 phobia among adults. Materials and methods:The sample of this descriptive and correlational study consisted of 545 people living in Kahramanmaras city center and meeting the study criteria. Study data were collected through google forms using personal information form, Health Literacy Scale and Coronavirus-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Yayla and İlgin [ 23 ] and Labrague and De Los Santos [ 24 ] indicated that nurses’ psychological well-being was significantly affected by coronaphobia. Although a recent study found that health literacy benefits the management of coronaphobia [ 25 ], the impact of eHL on coronaphobia during the pandemic has not been sufficiently studied. Considering that the pandemic has profoundly altered how people seek, use, and evaluate health care services, the role of eHL in this transformation should receive more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Yayla and İlgin [ 23 ] and Labrague and De Los Santos [ 24 ] indicated that nurses’ psychological well-being was significantly affected by coronaphobia. Although a recent study found that health literacy benefits the management of coronaphobia [ 25 ], the impact of eHL on coronaphobia during the pandemic has not been sufficiently studied. Considering that the pandemic has profoundly altered how people seek, use, and evaluate health care services, the role of eHL in this transformation should receive more attention.…”
Section: Introductionmentioning
confidence: 99%